Obstacles To Enhancing the Learning Environments of Infants in Day Care An Evaluation of Problems Perceived by Day Care Providers - Chambliss, Catherine ([S.l.] : Distributed by ERIC Clearinghouse, 1997)
This study focused on creating a liaison between day care providers and college developmental psychology researchers with the intent that day care providers would be able to share discoveries and develop expertise in challenging infants appropriately to encourage development. The project was collaborated on by college students and faculty; the day care providers were all females that volunteered to participate. Out of a sample population of 39 caregivers from 10 different day care centers, 20 were teachers and 19 were managers. They completed a survey that addressed three issues: (1) respondents' perceptions of infants' engagement in current programming; (2) level of teacher morale in infant classrooms; and (3) impressions of the quality of the atmosphere in infant classrooms. The results showed that the teachers and managers were concerned with: (1) problems with the staff (such as poor morale and little professional pride, and difficulty in planning classroom activities); (2) problems with the children (such as individual differences and predictable developmental challenges); and (3) problems with the parents (such as angry and critical parents, anxious and guilty parents, and neglectful parents). It was also found that the day care providers were interested in receiving additional training and desired to participate in the professionalization of day care provision. (Contains 14 references.) (DCP)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Caregiver Attitudes; Caregiver Child Relationship; Child Caregivers; Classroom Environment; Day Care; Day Care Centers; Infant Care; Infants; Parent Caregiver Relationship; Preschool Education; Infant Stimulation -- Professionalism; Reports, Research